A New Proposed Model of Public Expenditure - Kumar, Shakti; Yadav, Subhash Kumar (Indian Journal of Finance, 2017)
The present study endeavoured to propose a new mathematical formula based on Wagner’s law. Previous six versions of mathematical formulae, stated by different economists, were compared with a new proposed mathematical formula on the basis of three tests - spurious, stationary, and error correction method, taking data of Indian economy. All mathematical formulae, including the proposed one, found that Wagner’s law was applicable both in the short as well as in the long run in the Indian economy. However, the proposed model was able to give the highest speed of correcting error in comparison to the other models given earlier. Models given by Peacock-Wiseman (1961), Gupta (1967), Goffman (1968), Musgrave (1969), and Mann (1980) were able to give rate of correcting error less than the model proposed by us. The model given by Pryor (1969) was able to give rate of correcting error more than the model proposed by us, but residuals were not in a stationary state in the Pryor model, while these residuals were in the stationary state in our model. Therefore, the present study found that the proposed model was better in correcting errors in the Indian economy in comparison to other models.